(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Substance abuse refers to harmful or precarious use of psychoactive substances, including alcohol, cannabis and illicit drugs. It is directly and indirectly responsible for millions of morbidities each year. It is a crucial snag of present generation. Illegitimate use of psychoactive drugs can lead to lunatic illnesses. The prevalence of psychotic disorders among patients with substance abuse has attended noticeable magnitude. This study indicates that bipolar disorder is more likely to occur in patients with substance abuse. Chronic substance abuse can lead to down-regulation of concerned receptors as well as erosion of gray matter in the prefrontal cortex of brain. Hence, it would be imperative to address bipolar disorder from the perspective of potential and progressive adverse effect of substance abuse. The observation of study indicates that bipolar disorder is more prevalent in cannabis, alcohol and cocaine abuse cases. Drug abuse disorders are associated with impaired outcome of manic depression maladies that brings severe high or low moods, thinking and behavior.